Readiness for interprofessional learning among medical students: a scoping review protocol - Guardia de Barros, Thales; Argollo Ferreira, Fábio; Sanches Rodrigues, Marcos; Antônio Moura Gonzalez, Lucas; de Souza Menezes, João Daniel; de Almeida Sasso, Leonila Santos; Letícia dos Santos, Loiane; de Abreu Lima, Alba Regina; Sabadoto Brienze, Vânia Maria; Santana Gastardello Bizotto, Thaís; César André, Júlio; da Silva Fucuta, Patrícia (Acta Biomedica Atenei Parmensis, 2024)
Background and aim: Interprofessional education initiatives have been identified as promising strategies for providing high-quality, comprehensive, and effective health care. Interprofessional education can improve attitudes toward collaboration and teamwork during training, thereby improving attitudes toward interprofessional practice after graduation. Medicine and nursing are the fields most engaged in interprofessional education. Success in teaching and learning in this area depends on readiness for interprofessional education. Therefore, mapping this readiness among students may help higher education institutions establish or improve their respective approaches. The aim of this protocol is to map the literature to identify available evidence on the readiness for interprofessional learning among medical students. Research question: What data are available in the literature on readiness for interprofessional learning among medical students? Source of evidence: Literature search will be performed through the following databases: Scopus, Scientific Electronic Library Online (SciELO), PubMed, Biomed Central Journal, Wiley-Blackwell, Cumulative Index to Nursing and Allied Health Literature (CINAHL), and Education Resource Information Center (ERIC). Methods: This scoping review will be conducted in accordance with the Joanna Briggs Institute guidelines and the results, presented through a PRISMA flowchart. Review registration: Open Science Framework: https://osf.io/7acnq/.